Simian virus 40, poliovirus vaccines, and human cancer: research progress versus media and public interests - J.S. Butel (The World Health Organization, 2000)
From 1955 through early 1963, millions of people were inadvertently exposed to simian virus 40 (SV40) as a contaminant of poliovirus vaccines; the virus had been present in the monkey kidney cultures used to prepare the vaccines and had escaped detection. SV40 was discovered in 1960 and subsequently eliminated from poliovirus vaccines. This article reviews current knowledge about SV40 and considers public responses to reports in the media. SV40 is a potent tumour virus with broad tissue tropism that induces tumours in rodents and transforms cultured cells from many species. It is also an important laboratory model for basic studies of molecular processes in eukaryotic cells and mechanisms of neoplastic transformation. SV40 neutralizing antibodies have been detected in individuals not exposed to contaminated poliovirus vaccines. There have been many reports of detection of SV40 DNA in human tumours, especially mesotheliomas, brain tumours and osteosarcomas; and DNA sequence analyses have ruled out the possibility that the viral DNA in tumours was due to laboratory contamination or that the virus had been misidentified. However, additional studies are necessary to prove that SV40 is the cause of certain human cancers. A recently published review article evaluated the status of the field and received much media attention. The public response emphasized that there is great interest in the possibility of health risks today from vaccinations received in the past.